The effects of corporate social responsibility disclosure on firm performance with market share mediation - AM, Lutfirrahman; Saraswati, Erwin; Subekti, Imam (Journal of Accounting and Investment, 2024)
Research aims: This research aims to empirically examine and analyze the effects of CSR (Corporate Social Responsibility) disclosure on firm performance with market share mediation.Design/Methodology/Approach: The samples covered 38 firms enlisted in the Indonesia Stock Exchange with an observation period of five years. This research used multiple linear regression with the OLS (Ordinary Least Square) method to test the hypotheses.Research findings: The findings unveiled that the CSR disclosure partially improved the firm’s performance and market share.Theoretical contribution/Originality: Based on empirical evidence, the theories of stakeholder and legitimacy suggest that CSR disclosure improves firm performance, and the theories of legitimacy and market-based view advocate that CSR disclosure using market share can improve performance.Practitioner/Policy implication: These research results can be used as references for firms to implement better practices of CSR.Research limitation/Implication: This research is bound to subjectivity due to content analysis, in which the researchers had different understandings and perspectives on the research objects during the disclosure assessment.